Elevated CRP and IL6 Levels Predict Severe Cardiovascular Outcomes in COVID-19 Patients: Peningkatan Kadar CRP dan IL6 Memprediksi Hasil Kardiovaskular yang Parah pada Pasien COVID-19 - Ali Abdel Moneim Mohammed Hussain Al Khuzaie; Enas Abdul Kareem Jabbar; Bushra Jabbar Albadry (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the association between C-reactive protein (CRP) and interleukin 6 (IL-6) levels and cardiovascular complications in COVID-19 patients. Utilizing an ELISA kit for IL-6 and standard tests for CRP, we analyzed 192 samples, finding higher infection rates among the 50-69 age group, with significant prevalence of morbid obesity. Results showed a strong correlation between elevated CRP and IL-6 levels and the severity of cardiovascular complications, particularly in critical cases. These findings suggest that monitoring these biomarkers could be crucial for early intervention and managing cardiovascular risks in COVID-19 patients, potentially improving patient outcomes in clinical settings. Highlights: Biomarker Correlation: Elevated CRP and IL-6 levels are linked to severe cardiovascular complications in COVID-19 patients. Risk Management: Monitoring these biomarkers helps in early intervention and managing cardiovascular risks. Demographic Insights: The highest infection and complication rates are among the 50-69 age group with significant obesity. Keywords: COVID-19, Cardiovascular Complications, CRP, IL-6, Biomarker Monitoring